Increased Beat-to-Beat Blood Pressure Variability Is Associated With Impaired Cognitive Function. (25th September 2022) - Asmuje, Nur Fazidah; Mat, Sumaiyah; Goh, Choon Hian; Myint, Phyo Kyaw; Tan, Maw Pin
Abstract: BACKGROUND: Emerging evidence has linked visit-to-visit, day-to-day and 24-h ABPM blood pressure variability (BPV) with cognitive impairment. Few studies have, however, considered beat-to-beat BPV. This study, therefore, evaluated the relationship between beat-to-beat BPV and cognitive function among community-dwellers aged 55 years and over. METHODS: Data was obtained from the Malaysian Elders Longitudinal Research (MELoR) study, which employed random stratified sampling from three parliamentary constituencies within the Klang Valley. Beat-to-beat blood pressure (BP) was recorded using non-invasive BP monitoring (Taskforce TM, CNSystems). Low frequency (LF), high frequency (HF) and low-to-high frequency (LF:HF) ratio for BPV were derived using fast Fourier transformation. Cognition was evaluated using the Montreal Cognitive Assessment (MoCA) test, and categorized into normal aging, mild impairment and moderate-to-severe impairment. RESULTS: Data from 1, 140 individuals, mean age (SD) 68.48 (7.23) years, were included. Individuals with moderate-to-severe impairment had higher HF-BPV for systolic (SBP) and diastolic (DBP) blood pressure compared to individuals within the normal aging group [OR (95% CI) = 2.29 (1.62–3.24)] and [OR (95% CI) = 1.80 (1.32–2.45)], while HF-SBPV [OR (95% CI) = 1.41 (1.03–1.93)] but not HF-DBPV was significantly higher with mild impairment compared to normal aging after adjustments for potential confounders. Moderate-to-severe impairment was associated with significantly lower LF:HF-SBPV [OR (95% CI) = 0.29 (0.18–0.47)] and LF:HF-DBPV [OR (95% CI) = 0.49 (0.34–0.72)], while mild impairment was associated with significantly lower LF:HF-SBPV [OR (95% CI) = 0.52 (0.34–0.80)] but not LF:HF-DBPV [OR (95% CI) = 0.81 (0.57–1.17)], compared to normal aging with similar adjustments. CONCLUSION: Higher HF-BPV, which indicates parasympathetic activation, and lower LF:HF-BPV, which addresses sympathovagal balance, were observed among individuals with moderate-to-severe cognitive impairment. Future studies should determine whether BPV could be a physiological marker or modifiable risk factor for cognitive decline. Graphical Abstract: